INHIBITORY EFFECT OF ASCORBIC ACID MICROEMULSION ON PHOTO-OXIDIZED VIRGIN COCONUT OIL - Rukmini, Ambar (Universitas Widya Mataram, 2016)
The effect of water-in-oil (w/o) microemulsion containing ascorbic acid on photo-oxidative stability of virgin coconut oil (VCO) was investigated. To optimize the formulation, w/o microemulsions were prepared using hydrophilic lipophilic balance (HLB) concept, consisted of ternary nonionic surfactants having low, medium, and high HLB values. From this optimum HLB number, the ratio of water, surfactant and oil was determined to obtain microemulsion areas. After optimization of the microemulsion system, the storage at room temperature, and the extreme condition were conducted for testing the microemulsion stability. Then, the stable formulas were used for delivering ascorbic acid. The solubility and photo-oxidative stability of ascorbic acid microemulsion were evaluated. The optimum formula of ascorbic acid microemulsion was applied into VCO at various concentrations (0, 1, 5, and 10% w/w). Samples were subjected to photo-oxidation under fluorescent light exposure of 4000 lux for up to 8 hours. Peroxide values (PVs) and p-anisidine values (p-AnVs) of the samples were measured at 1 hour interval. The results indicated that w/o microemulsion could be formed on the HLB number of 7. W/o microemulsion containing 75% oils need surfactant concentrations of ≥ 4.5 part of water, and if containing 77.78% oils, the surfactant concentration must ≥ 5.5 part of water. These microemulsions remained stable during storage at room temperature, even after centrifugation, but did not tolerate at high temperature. The maximum solubility of ascorbic acid in w/o microemulsion was 1%. Ascorbic acid microemulsion resistant to photo-oxidation and effective inhibits that reaction in VCO. This study confirmed that w/o microemulsion can act as ascorbic acid delivery system to disperse into VCO for inhibiting its’ quality deterioration due to photo-oxidation.